2013
DOI: 10.2979/africatoday.60.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Imagining Emigration: Debating National Duty in Eritrean Classrooms

Abstract: Emigration is effectively illegal in Eritrea; however, Eritrea cultivates a loyal, active diaspora. Graduated emigration policies create a territorially bound population to provide cheap labor to the state and a diaspora that contributes financial resources to the government. The celebration of diasporic nationalism has successfully produced a longing to return among the diaspora, but it has inadvertently produced a longing to leave among Eritreans trapped in Eritrea. These contradictions are explored by exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Complicating the contemporary moral and political economy of exit from Eritrea further is also the fact that while the right to exit continues to be denied for most people, there is a growing sense of a responsibility to exit. Leaving has come to be seen as a way of fulfilling national and personal responsibilities through remittances and transnational investments, a sense that the Eritrean government itself reinforces (AuthorY, 2019;Riggan, 2013). At a familial level, our research with families within Eritrea has revealed the whole spectrum of attitudes towards migration, from families who strongly and persistently discourage other family members from leaving, to those families that expect the oldest siblings in particular to leave the country in search of employment and opportunities for future family reunification (Author X, 2019).…”
Section: The Ambivalent Logics Of Eritrean Exit Regulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complicating the contemporary moral and political economy of exit from Eritrea further is also the fact that while the right to exit continues to be denied for most people, there is a growing sense of a responsibility to exit. Leaving has come to be seen as a way of fulfilling national and personal responsibilities through remittances and transnational investments, a sense that the Eritrean government itself reinforces (AuthorY, 2019;Riggan, 2013). At a familial level, our research with families within Eritrea has revealed the whole spectrum of attitudes towards migration, from families who strongly and persistently discourage other family members from leaving, to those families that expect the oldest siblings in particular to leave the country in search of employment and opportunities for future family reunification (Author X, 2019).…”
Section: The Ambivalent Logics Of Eritrean Exit Regulationsmentioning
confidence: 99%
“…Policies towards the diaspora also reinforce a tiered system of citizenship whereby Eritreans outside of the country who pay 2 percent of their income to the Eritrean government may have more freedom to travel in and out of Eritrea and be exempted from national service, whilst those who remain in Eritrea have restricted freedom of movement and are enrolled indefinitely in government employment (Riggan, 2013;Woldemikael, 2018).…”
Section: The Ambivalent Logics Of Eritrean Exit Regulationsmentioning
confidence: 99%
“…The notion of hollow nationalism is inspired by Ritty Lukose's () discussion of “empty citizenship.” Elsewhere, I have focused more extensively on the subtle and covert forms of counterideology that emerged in the face of the hollowing out of official nationalism. I have examined how hybrid nationalism was formed by Eritreans born in Ethiopia (Riggan ), how teachers construct notions of national identity for educated citizens (Riggan , ), and how students attempt to carve out a sense of national identity that is based on desires to emigrate (Riggan in press).…”
mentioning
confidence: 99%